1989
DOI: 10.1144/gsjgs.146.6.0971
|View full text |Cite
|
Sign up to set email alerts
|

Seismic velocities from the Kohistan Volcanic Arc, northern Pakistan

Abstract: The rocks bounded by the Main Mantle Thrust and the Northern Suture in northern Pakistan constitute an exhumed section through a Cretaceous volcanic arc. Samples have been collected from all the principal lithological groups of the arc, and P and S-wave seismic velocities have been measured in the laboratory with the prime objective of comparing the velocities with those determined by seismic refraction experiments on modern volcanic arcs. Velocities were measured at up to 0.7 GPa and consideration has been gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Such structures are not found in all arcs, not being present, for example, in seismic sections of the Aleutian arc (Fliedner & Klemperer 1999;Holbrook et al 1999). P-wave velocities of 6.0-6.5 km s -1 are characteristic of virtually all intermediate and granitic plutonic rocks found in the arc environment (Chroston & Simmons 1989;Miller & Christensen 1994;Christensen & Mooney 1995), and it is highly likely that the mid-crustal layer in the South Sandwich arc consists of such intermediategranitic plutonic rocks (Larter et al 2001). Suyehiro et al (1996) interpreted the midcrustal layer in the Izu-Ogasawara arc as tonalitic, based on lateral correlation of the seismically identified layer with tonalitic outcrops.…”
Section: Crustal Structure From Seismic Studiesmentioning
confidence: 99%
“…Such structures are not found in all arcs, not being present, for example, in seismic sections of the Aleutian arc (Fliedner & Klemperer 1999;Holbrook et al 1999). P-wave velocities of 6.0-6.5 km s -1 are characteristic of virtually all intermediate and granitic plutonic rocks found in the arc environment (Chroston & Simmons 1989;Miller & Christensen 1994;Christensen & Mooney 1995), and it is highly likely that the mid-crustal layer in the South Sandwich arc consists of such intermediategranitic plutonic rocks (Larter et al 2001). Suyehiro et al (1996) interpreted the midcrustal layer in the Izu-Ogasawara arc as tonalitic, based on lateral correlation of the seismically identified layer with tonalitic outcrops.…”
Section: Crustal Structure From Seismic Studiesmentioning
confidence: 99%
“…All of these examples are thought to have been intraoceanic. The Kohistan arc, in particular, has provided critical information on the seismic and petrological structure of arc crust (Chroston & Simmons 1989;Miller & Christensen 1994). DeBari & Sleep (1991) demonstrated that the Talkeetna arc can be used for mass-balance calculations to determine the composition of mantle-derived magma feeding the arc, and argued that it was high-Mg (and low-A1) basalt.…”
Section: Exhumed Intra-oceanic Arcsmentioning
confidence: 99%
“…Although surface phenomena and seismic studies allow for interpretation of transform boundaries, deformation and steeply dipping structures lead to some ambiguity. Chroston and Simmons [1989] reported laboratory-measured seismic velocities of samples from, and constructed a seismic velocity model for, the Kohistan arc. South of the Chilas Complex is a belt of mafic to dioritic sills and metamorphosed volcanic rocks that have been all grouped into a single unit called the Kamila Amphibolites or alternatively the "Kamila Shear Zone," which has been interpreted as the downfolded equivalents of the Chalt supracrmtal sequence to the north that have been overthickened by thrust faulting [Treloar et al, 1990].…”
Section: •Now At Ocean Drillling Progrmn College Station Texasmentioning
confidence: 99%
“…Further complications obscure most of the processes involved in the growth and evolution of landforms at convergent boundaries due to the great depths at which these activities occur, depths that generally defy resolution of petrogenetic processes by remote sensing techniques, and / Jijal Complex crustal mafic cumulate complex. The model of Chroston and Simmons [1989] invokes a crustal thickness of 30 km, extracted from the combined work of Bard et al [ 1980] for the lower part of the section and Coward et al [ 1982] for the upper part. South of the Kamila group is the Jijal ultramafic-mafic lower crustal cumulate complex, which comprises the focus of this research.…”
Section: •Now At Ocean Drillling Progrmn College Station Texasmentioning
confidence: 99%